Wake symmetrization of a bluff Ahmed body based on sliding mode control. Issue 2 (2020) - Mariette, K.; Bideaux, É.; Bribiesca-Argomedo, F.; Ébérard, D.; Sesmat, S.; Haffner, Y.; Borée, J.; Castelain, T.; Michard, M.
Abstract: Aerodynamic drag reduction is needed to develop future fuel efficient ground transportation vehicles. Our study targets bluff bodies with wake asymmetries due to natural bistability or cross wind contributing to the drag increase at high velocities. The originality of this work is to apply closed loop control techniques based on sliding mode control theory and a Smith like predictor scheme for delay compensation in order to force the wake symmetry. This non linear controller was tuned thanks to experimental study of pulsed jet actuators placed at the back of a modified Ahmed bluff body and shows that wake symmetrization can be achieved either in aligned or cross wind configurations.